The Inherent Faults of the State Pension System and the Main Direction of its Improvement - Banyár, József (Public Finance Quarterly, 2019)
In my study, I took into account the design faults of the state-funded, pay-as-you-go system and realised that its principle (created in arrears) is defective, and it is necessary to move to a new operating principle to correct it. We have to forget about the existing so-called ‘unfunded’ pension system, and the state pension system shall be explicitly placed on its real basis, human capital. This results in an automatic asset/liability matching that is currently totally missing, and we can forget about the usual debates about the sustainability of the pension system. The result of such a system would probably be an increase in the number of births compared to today, but this is not the purpose of the proposed reform, which I intend to elaborate in a separate study, i.e. how this can be put into practice.